Effect of motivational interviewing on self-management in patients with type 2 diabetes mellitus: A meta-analysis - Dan Song; Tu-Zhen Xu; Qiu-Hua Sun (Elsevier, 2014)
Objective: The objective of this meta-analysis was to evaluate the effect of motivational interviewing (MI) on self-management in patients with type 2 diabetes. Methods: Randomised controlled trials that assessed the effects of MI on self-management and HbA1c levels in patients with type 2 diabetes were systematically reviewed using multiple electronic databases. Weighted mean differences with 95% confidence intervals were calculated for continuous data. Results: Ten trials were included in this meta-analysis. The self-management ability of patients with type 2 diabetes who underwent MI was significantly better than that of patients in the control group (WMD, 2.37; 95% CI, 1.77-2.98; p < 0.00001). Subgroup analysis showed that short-term MI (≤6 months) resulted in a significant decrease in the HbA1c level (p < 0.05) but that this advantage was not present for relatively long-term MI (>6 months) (p > 0.05). Conclusions: MI was associated with improved self-management abilities among patients with type 2 diabetes, and short-term MI (≤6 months) effectively decreased the HbA1c level. The effect of long-term MI (>6 months) on the HbA1c level remains uncertain. Large-scale, higher-quality randomised controlled trials are needed to confirm the present findings.